2011
DOI: 10.6090/jarq.45.197
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Photoregime on the Calling Behavior of the Rice Leaf Folder Moth, Cnaphalocrocis medinalis (Lepidoptera: Crambidae)

Abstract: The rice leaf folder, Cnaphalocrocis medinalis, showed a circadian rhythm in its calling behavior at 25 ± 1 o C. Female moths showed calling behavior most frequently 5-7 h into the scotophase under LD 15:9. Female moths at age 4 (days), after entraining at LD 15:9, showed a free-running rhythm for at least two more cycles in continuous darkness. The rhythm was damped out in constant light. The temporal pattern in the calling behavior was affected by different LD cycles (LD 15:9, 12:12, and 9:15), indicating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
(34 reference statements)
2
5
0
Order By: Relevance
“…Calling females exhibited a characteristic posture that consists in extruding and bending the abdominal tip toward the dorsal surface. This posture is similar to that reported for other crambid moths such as the yellow peach moth Dichocrocis punctiferalis Guenée (Konno et al 1980), the rice leafroller Cnaphalocrocis medinalis Guenée (Kawazu et al 2011), and the cucumber moth Diaphania indica (Saunders) (Kinjo & Arakaki 1997).…”
Section: Resultssupporting
confidence: 73%
“…Calling females exhibited a characteristic posture that consists in extruding and bending the abdominal tip toward the dorsal surface. This posture is similar to that reported for other crambid moths such as the yellow peach moth Dichocrocis punctiferalis Guenée (Konno et al 1980), the rice leafroller Cnaphalocrocis medinalis Guenée (Kawazu et al 2011), and the cucumber moth Diaphania indica (Saunders) (Kinjo & Arakaki 1997).…”
Section: Resultssupporting
confidence: 73%
“…They found that the amount of Z9-16:Ald in H. assulta peaked 4 h after the lights were turned off, and remained at this level for 4 h. In contrast, Kamimura & Tatsuki (1993) found that the sex pheromone titer of H. assulta reached a maximum at 2 h after lights had been turned off and remained at this level for 4 h, and they found that only a small amount of sex pheromone was detected during the photophase. Sex pheromone level usually increases during the scotophase and decreases during the photophase (Schal & Cardé 1986;Raina et al 1991;Kou 1992;Dong & Du 2001;Kawazu & Tatsuki 2002;Kawazu et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies illustrated that the daily rhythm of sexual activity, such as calling activity and pheromone production and release, was usually dependent upon endogenous (neural, hormonal) and exogenous factors (photoperiod, temperature) (Hollander & Yin 1982;Raina & Klun 1984;Delisle & McNeil 1987;Raina 1993). Sex pheromone level and calling percentage usually decrease during the photophase, falling to nearly zero by the onset of the scotophase, before increasing again during the scotophase (Schal & Cardé 1986;Delisle & McNeil 1987;Kou 1992;Kamimura & Tatsuki 1994;Dong & Du 2001;Kawazu & Tatsuki 2002;Xiang et al 2010;Kawazu et al2011), and the circadian rhythm of female calling and sex pheromone production and release may be entrained by the photoregime (Kamimura & Tatsuki 1994;Kawazu et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…The daily rhythm of sexual activity in moths, including calling activity and pheromone production and release, is usually dependent upon endogenous (neural, hormonal) and exogenous factors (photoperiod, temperature) (Hollander & Yin, ; Raina & Klun, ; Delisle & McNeil, ; Raina, ). The copulations of nocturnal moths show circadian rhythms and usually occur at dawn and dusk (Schal & Cardé, ; Kamimura & Tatsuki, ; Burks et al ., ; Kawazu et al ., ; Yan et al ., ; Li et al ., ), and the circadian clock genes in compound eyes may participate in synchronizing the rhythm of mating behavior to light‐dark cycles. Meanwhile, we initially confirmed that Ha‐per tended to be down‐regulated following starvation.…”
Section: Discussionmentioning
confidence: 99%